NARRATIVE STRUCTURE ANALYSIS OF PALM TREE MYTH IN PEDAWA VILLAGE, BANJAR DISTRICT, BULELENG REGENCY - Nyoman Yulia Pratiwi; Maria Matildis Banda; I Ketut Sudewa (Yavana Bhasha : Journal of English Language Education, 2023)
Pedawa Village, located in Banjar District, Buleleng Regency, owns a myth about the palm tree growth in the village, which was told from one generation to another. The myth becomes guidelines for the villagers which is still applied at the present day. The purpose of the research is to break down the myth based on its narrative structure forms. To break down the myth the theory of narrative structure from Roland Barthes and Alan Dundes is used. Through the analysis process, it is revealed that this myth consisted of main function and catalytic function. Aside from that, the myth is also consisted of motifeme structure. The two breaking down processes proved that the myth fulfills the temporal and causality order. Keyword: myth, Pedawa, palm tree, narrative, structure